Research Progress on the Effect of Exercise Rehabilitation on Functional Level and Physical Fitness - YIN Lianhua; ZHENG Yan; WU Lijuan; NI Xuling; CHEN Lidian (康复学报)
The essence of rehabilitation is the recovery and reconstruction of body function,and cardiopulmonary function is not only the core of body function, but also the core element of physical fitness. As one of the important interventions of modern rehabilitation treatment, exercise rehabilitation is the fundamental way to improve the level of body function, and plays a key role in the process of disease rehabilitation. The forms of exercise rehabilitation are widely used in clinic including aerobic exercise, high intensity interval training,muscle strength training, and traditional exercise and so on. Different forms of exercise rehabilitation can improve the level of body function and promote physical fitness in varying degrees. The main functions include regulating blood pressure, blood lipids and blood glucose, improving balance and muscle strength,increasing bone mineral density, enhancing cardiorespiratory fitness and walking ability, improving cognitive and memory functions,regulating emotions, promoting mental health, and improving the quality of life, etc., so as to achieve the goal of shortening the process of disease rehabilitation and improving its curative effect. However, there are differences in the dimensions and degrees of the influence of different forms of exercise rehabilitation on functional level and physical fitness. Among them, aerobic exercise mainly has a positive impact on cardiorespiratory fitness, glucose and lipid metabolism,emotional regulation, cognition and memory and other dimensions, and its mechanism involves the increase of endogenous cannabinoid in circulation and the integrity of white matter fibers and so on. Compared with moderate intensity aerobic exercise, high intensity interval training can improve cardiorespiratory fitness and cardiac metabolic health more timely and its mechanism involves the increase of muscle mitochondrial production capacity and the regulation of partial gene expression in skeletal muscle. Muscle strength training can improve blood glucose control and reduce the risk of chronic diseases and death by increasing muscle strength and endurance, especially for postmenopausal women and overweight/obese elderly. Traditional exercises, such as Taijiquan and Baduanjin, are important interventions of rehabilitation in traditional Chinese medicine, which have definite effect in improving balance, cognition and memory, and are worthy of clinical promotion and application. At present, how to choose the best form of exercise rehabilitation and the best course of treatment for people with different functional disorders and different disease status remains to be further clarified by follow-up clinical and basic research.